AAHHHHHHHHHHHHHHHHHH
![AAHHHHHHHHHHHHHHHHHH class=](https://us-static.z-dn.net/files/ddc/c86d5b648a545cc665d6ab2bcbcb1155.png)
Step-by-step explanation:
[tex] \dfrac{1 - \cos \theta}{1 + \cos \theta} = \dfrac{\sec \theta - 1}{\sec \theta + 1} [/tex]
[tex] \dfrac{1 - \cos \theta}{1 + \cos \theta} = \dfrac{\frac{1}{\cos \theta} - 1}{\frac{1}{\cos \theta} + 1} [/tex]
[tex] \dfrac{1 - \cos \theta}{1 + \cos \theta} = \dfrac{\cos \theta}{\cos \theta} \times \dfrac{\frac{1}{\cos \theta} - 1}{\frac{1}{\cos \theta} + 1} [/tex]
[tex] \dfrac{1 - \cos \theta}{1 + \cos \theta} = \dfrac{\frac{\cos \theta}{\cos \theta} - \cos \theta}{\frac{\cos \theta}{\cos \theta} + \cos\theta} [/tex]
[tex] \dfrac{1 - \cos \theta}{1 + \cos \theta} = \dfrac{1 - \cos \theta}{1 + \cos\theta} [/tex]